Kepentingan Amerika Serikat dalam Proses Denuklirisasi Korea Utara - Javira Ardiani (Frequency of International Relations (FETRIAN), 2020)
The United States is a country that seeks to realize denuclearization in Korean Peninsula. Though the United States is not a party that will be directly threatened because the United States have more stronger nuclear capability than North Korea’s nuclear. This study aims to describe the interests of the United States as a Status Quo State in the process of denuclearization of North Korea. The conceptual framework used by this study is Randall L. Schweller's Range of State Interest concept. This research uses a qualitative research method with descriptive analytical research that uses secondary data. Based on the concept of Range of State Interest, this research found that the United States as a 'Lion' country has an interest in maximizing security which includes maintaining its identity as a nuclear possession country, maintaining trade with East Asian countries, and improving governmental functions. Whereas in maintaining its position, the United States has an interest in maintaining its alliance with South Korea and Japan, maintaining prestige for world peace, and realizing CVID (Complete, Verifiable, and Irreversible Dismantlement) or full denuclearization.